조개의 상징에 관한 연구 - 이혜경 (심리상담 및 모래놀이치료(구 학교상담 및 모래놀이), 2023)
본 연구는 연구자의 모래놀이치료 상담과정에서 내담자가 자주 사용했던 소품 중 하나인 조개의 생물학적 특성을 알아보고 조개가 갖고 있는 의미를 종교, 설화, 인류사, 한국문화 속에서 알아보고 임상적 시사점을 살펴보고자 한다. 조개는 재생과 부활, 치유와 구원의 상징을 갖는다. 조개는 다산과 풍요로움, 여성성을 상징하며, 길조와 주술적인 힘의 상징을 의미한다. 또한, 조개는 자원을 나타내는 대표적인 상징으로 조개화폐, 밥조개로 표현되었고 사람들의 주요한 양식으로 나타나고 있다. 조개는 외부로부터 들어온 이물질을 고스란히 받아들여 오랜 시간 품고 둥근 보석의 결정체인 진주를 만들어낸 것이 가치를 더해준다. 고통과 인내의 상징을 의미한다. 종합하면 조개는 치유, 재생, 여성성, 내적자원, 성장 등 다양한 상징을 보여주고 있으며 본 연구자의 내담자들은 이러한 측면을 조개를 사용하여 모래작품에서 표현하였다. This study aims to examine the meaning of shellfish, one of the props frequently used by clients in the consultation process of sand play therapy, in religion, folklore, human history, and Korean culture, and to examine clinical implications. Shellfish have a symbol of regeneration and resurrection, healing and salvation. Shellfish symbolizes fertility, abundance and femininity, and is a symbol of auspiciousness and magical power. In addition, shellfish are represented as shellfish currency and scallops as a representative symbol of resources, and they appear as the main form of people. The fact that shellfish receives foreign substances from the outside and embraces it for a long time to create pearls, the crystals of round gems, adds value. It is a symbol of suffering and perseverance. Taken together, shellfish show various symbols such as healing, regeneration, femininity, internal resources, and growth, and this aspect of this researcher's clients expressed in sand works using shellfish. KCI Citation Count: 0